Molecular mechanistic pathways underlying the anticancer therapeutic efficiency of romidepsin - El Omari, Nasreddine; Lee, Learn-Han; Bakrim, Saad; Makeen, Hafiz A; Alhazmi, Hassan A; Mohan, Syam; Khalid, Asaad; Long, Chiau Ming *; Bouyahya, Abdelhakim (Elsevier, 2023)
Romidepsin, also known as NSC630176, FR901228, FK-228, FR-901228, depsipeptide, or Istodax®, is a natural molecule produced by the Chromobacterium violaceum bacterium that has been approved for its anti-cancer effect. This compound is a selective histone deacetylase (HDAC) inhibitor, which modifies histones and epigenetic pathways. An imbalance between HDAC and histone acetyltransferase can lead to the down-regulation of regulatory genes, resulting in tumorigenesis. Inhibition of HDACs by romidepsin indirectly contributes to the anticancer therapeutic effect by causing the accumulation of acetylated histones, restoring normal gene expression in cancer cells, and promoting alternative pathways, including the immune response, p53/p21 signaling cascades, cleaved caspases, poly (ADP-ribose) polymerase (PARP), and other events. Secondary pathways mediate the therapeutic action of romidepsin by disrupting the endoplasmic reticulum and proteasome and/or aggresome, arresting the cell cycle, inducing intrinsic and extrinsic apoptosis, inhibiting angiogenesis, and modifying the tumor microenvironment. This review aimed to highlight the specific molecular mechanisms responsible for HDAC inhibition by romidepsin. A more detailed understanding of these mechanisms can significantly improve the understanding of cancer cell disorders and pave the way for new therapeutic approaches using targeted therapy.